Vascular and extravascular immunoreactivity for intercellular adhesion molecule 1 in the orbitofrontal cortex of subjects with major depression: Age-dependent changes - Miguel-Hidalgo, Jose Javier; Overholser, James C.; Jurjus, George J.; Meltzer, Herbert Y.; Dieter, Lesa; Konick, Lisa; Stockmeier, Craig A.; Rajkowska, Grazyna (Journal of affective disorders, 2011)
Vascular and immune alterations in the prefrontal cortex may contribute to major depression in elderly subjects. Intercellular adhesion molecule-1 (ICAM-1), major inflammatory mediator in vessels and astrocytes, could be altered in geriatric depression, but little is known about its age-dependent expression in subjects with depression and its relationship to astrocytes identified by the marker glial fibrillary acidic protein (GFAP), found to be reduced in depression. We measured the percentage of gray matter area fraction covered by ICAM-1 immunoreactivity in blood vessels and in extravascular accumulations of ICAM-1 immunoreactivity in 19 non-psychiatric comparison subjects and 18 subjects with major depression, all characterized by postmortem psychological diagnosis. Association of extravascular ICAM-1 to GFAP-positive astrocytes was investigated by double-labeling immunofluorescence. Vascular and extravascular fractions of ICAM-1 immunoreactivity were lower in subjects with MDD than in non-psychiatric comparison subjects. Non-psychiatric comparison subjects older than 60 experienced dramatic increase in extravascular ICAM-1 immunoreactivity, but this increase was attenuated in elderly subjects with MDD, particularly in those dying by suicide. Most extracellular ICAM-1 immunoreactivity was coextensive with GFAP-immunoreactive astrocytes in both groups. Heterogeneity in type and dosage of antidepressant medication. Difficulty in determining the exact onset of depression in subjects older than 60 at the time of death . Routine cerebrovascular pathological screening may miss subtle subcellular and molecular changes. There is significant attenuation of extravascular and vascular ICAM-1 immunoreactivity in elderly subjects with major depression suggesting an astrocyte-associated alteration in immune function in the aging orbitofrontal cortex of subjects with MDD.